Comparative safety of tyrosine kinase inhibitors in the treatment of metastatic renal cell carcinoma: a systematic review and network meta-analysis - Krawczyk, Kinga; Śladowska, Katarzyna; Holko, Przemysław; Kawalec, Paweł (Frontiers in Pharmacology, 2023)
Objective: This study aimed to compare the safety profile of tyrosine kinase inhibitors (TKIs) approved for use as monotherapy or combination therapy for the first-line treatment of adult patients with metastatic clear cell renal cell carcinoma (RCC). Methods: A systematic review with frequentist network meta-analysis (NMA) was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We included randomized controlled trials (RCTs) investigating the use of: cabozantinib, pazopanib, sorafenib, sunitinib, tivozanib, cabozantinib + nivolumab, lenvatinib + pembrolizumab, axitinib + avelumab, and axitinib + pembrolizumab in previously untreated adult patients with metastatic clear cell RCC. Eligible studies were identified by two reviewers in MEDLINE (via PubMed), EMBASE, and Cochrane Library. The risk of bias for RCTs was assessed using the Cochrane Collaboration tool. The P score was used to determine the treatment ranking. The mean probability of an event along with the relative measures of the NMA was considered with the treatment rankings. Results: A total of 13 RCTs were included in the systematic review and NMA. Sorafenib and tivozanib used as monotherapy were the best treatment options. Sorafenib achieved the highest P score for treatment discontinuation due to adverse events (AEs), fatigue, nausea, vomiting of any grade, and hypertension of any grade or grade ≥3. Tivozanib achieved the highest P score for AEs, grade ≥3 AEs, dose modifications due to AEs, and grade ≥3 diarrhea. Sunitinib was the best treatment option in terms of diarrhea and dysphonia of any grade, while cabozantinib, pazopanib, and axitinib + pembrolizumabin terms of grade ≥3 fatigue, nausea, and vomiting. TKIs used in combination were shown to have a poorer safety profile than those used as monotherapy. Lenvatinib + pembrolizumab was considered the worst option in terms of any AEs, grade ≥3 AEs, treatment discontinuation due to AEs, dose modifications due to AEs, fatigue of any grade, nausea, vomiting, and grade ≥3 nausea. Axitinib + avelumab was the worst treatment option in terms of dysphonia, grade ≥3 diarrhea, and hypertension, while cabozantinib + nivolumab was the worst option in terms of grade ≥3 vomiting. Interestingly, among the other